1950
DOI: 10.1002/ange.19500622004
|View full text |Cite
|
Sign up to set email alerts
|

Sterische Hinderung und cis, trans‐Isomerie bei der Dienreaktion konjugiert‐ungesättigter Fettsäuren Die Pandienzahl

Abstract: Zur Illustration der Brauchbarkeit unserer Methode sind noch weitere Diagramme wiedergegeben, die in folgender einfacher Weise reproduziert wurden: Man legte die nach der Rubeanwasserstoff-Behandlung durch Baden in 1 n-Soda-Losung und Wasser vorn Farbstoff vollig befreiten, trocknen Papiere in einen Kopierrahmen auf Bromsilberpapier und belichtet, nachdem man die obere Yante der Yupferfront durch einen horizontalen Schwarzpapierstreifen eben abgedeckt hat, etwa 10 sec. Die abgebildeten Diagramrnezeigen nun die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1952
1952
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This has beeal observed with the conjugated linoleates by Nichols et al (10) and by yon Mikusch (11). This has beeal observed with the conjugated linoleates by Nichols et al (10) and by yon Mikusch (11).…”
Section: Alpha and Beta Eleostearic Acidsmentioning
confidence: 69%
See 2 more Smart Citations
“…This has beeal observed with the conjugated linoleates by Nichols et al (10) and by yon Mikusch (11). This has beeal observed with the conjugated linoleates by Nichols et al (10) and by yon Mikusch (11).…”
Section: Alpha and Beta Eleostearic Acidsmentioning
confidence: 69%
“…It has also been observed by Alder and Yogt (12), with simple aliphatic dieues, such as hexadiene 2,4. c) Beta eleostearic acid is more reactive than the a acids in the Diels-Alder addition reaction. These facts indicate the all-trans structure of fl eleostearate for the following reasons: vod Mikusch (11) has recerttly shown that the eis, trans conjugated linoleates react very slowly if at all with maleic anhydride at temperatures of about 100 ~ or lower whereas the trans, trans isomers react readily in the diene number determination under these conditions. Its ester polymerized with heat twice as fast as the a ester (13).…”
Section: Alpha and Beta Eleostearic Acidsmentioning
confidence: 97%
See 1 more Smart Citation
“…From this the position of the double bond closest to the carboxyl group is between the 8th and 9th carbon atom while the iodometrie and dienometric behavior, which was typical for a conjugated diene, fixed the position of the second double bond between the 10th and llth carbon atom. The identity of diene value and pandiene value is considered sufficient proof of the trans,trans-strueture in view of the arguments published elsewhere (6).…”
Section: Summary Of Experimental Workmentioning
confidence: 85%
“…This causes strong sterical interactions during a cisoid orientation of the diene which is proposed for the transition state of a Diels–Alder reaction. The addition of catalytic amounts of iodine can overcome this problem, as it leads to an isomerisation of the E , Z ‐ to the E , E ‐isomers , which allows to decrease the reaction temperature. A further decrease of the reaction temperature can be achieved with the help of Lewis‐acid catalysts .…”
Section: Introductionmentioning
confidence: 99%